Gephyrin phosphorylation in the functional organization and plasticity of GABAergic synapses - Zacchi, Paola; Antonelli, Roberta; Cherubini, Enrico (Frontiers in Cellular Neuroscience, 2014)
Gephyrin is a multifunctional scaffold protein essential for the postsynaptic accumulation of inhibitory glycine and GABAA receptors at synaptic sites. The molecular events involved in gephyrin-dependent GABAA receptor clustering are still unclear. Evidence has been recently provided that gephyrin phosphorylation plays a key role in these processes. By impinging upon its post-synaptic scaffolding properties as well as its stability, gephyrin post-translational modifications have been shown to impact on the structural remodeling of GABAergic synapses leading to synaptic plasticity. In addition, not only gephyrin phosphorylation per se but also the subsequent phosphorylation-dependent recruitment of the chaperone molecule Pin1 represents an emerging mechanism to regulate GABAergic signaling. Extensively characterized as pivotal enzyme controlling cell proliferation and differentiation, the prolyl-isomerase activity of Pin1 has been shown to regulate protein synthesis necessary to sustain the late phase of long-term potentiation at excitatory synapses, thus suggesting its involvement at synaptic sites. In this review we will summarize the current state of knowledge on the signaling pathways responsible for gephyrin post-translational modifications. We will also outline future lines of research that might contribute to better unveil the molecular mechanisms by which gephyrin regulates synaptic plasticity processes at GABAergic synapses.